Mediating Effects of Plasma Metabolites in Inflammatory Protein- Lymphoma Causality: A Mendelian Randomization Study - Ji, Yueru; Gao, Xiaotong; Liu, Li; Wan, Zhuo; Qin, Weiwei (Current Medicinal Chemistry, 2025)
<span class=
Keywords: mendelian randomization